Ensuring Resilience in Microservices with Cloud-Native API Gateways - Vijay Kumar Pasunoori (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The article examines the critical role of cloud-native API gateways in ensuring resilience within microservices architectures. Drawing from comprehensive studies across 145 organizations and analysis of 892 software practitioners, the article demonstrates how microservices adoption has transformed modern application development, with adoption rates reaching 89% in financial services, 76% in retail, and 71% in healthcare sectors. It presents empirical evidence of significant improvements, including a 71% decrease in deployment time and 68% reduction in system downtime compared to monolithic architectures. Through analysis of production environments spanning 178 organizations, the article reveals that API gateways achieve 99.95% service availability and can handle up to 250,000 requests per second during peak loads. The article explores advanced features including circuit breaking patterns, which reduce cascading failures by 83.5%, and intelligent load balancing strategies that improve resource utilization by 88%. Additionally, it examines the business impact through metrics demonstrating substantial improvements in system uptime, incident response times, and infrastructure costs.